Faktor- Faktor yang Berhubungan dengan Kejadian Dismenore pada Siswi di SMA Negeri I Lalan Kabupaten Musi Banyuasin Tahun 2025 - Sardiana, Dita; Indiriani, Putu Lusita Nati; Rahmawati, Eka; Angraini, Arie (Lembaga Pengembangan Kinerja Dosen, 2026)
Adolescence is a transitional period from childhood to adulthood characterized by physical, psychological, and social changes. One significant phenomenon in female adolescents is menstruation, which is often accompanied by dysmenorrhea or menstrual pain. Dysmenorrhea is a common reproductive health problem, with a prevalence of more than 60% in Indonesia. This condition not only causes discomfort but may also affect daily activities, reduce concentration, and hinder academic performance. Several factors are assumed to be associated with dysmenorrhea, including menstrual duration, nutritional status, and exercise habits. This study aimed to determine the relationship between menstrual duration, nutritional status, and exercise habits with the incidence of dysmenorrhea among female students at SMA Negeri 1 Lalan, Musi Banyuasin Regency, in 2025. The research employed a quantitative method with an analytical survey and a cross-sectional design. The population consisted of 157 students, with a sample of 113 respondents selected using the Slovin formula. Data were collected using questionnaires and Body Mass Index (BMI) measurements, and analyzed with the chi-square test at a 0.05 significance level. The results showed that menstrual duration (p = 0.181) and nutritional status (p= 0.095) had no significant association with dysmenorrhea, while exercise habits were significantly associated (p = 0.030). These findings highlight the importance of physical activity in preventing dysmenorrhea and are expected to provide valuable input for schools and health workers in reproductive health promotion programs.”